Museum-archived and recent acquisition nitrates from the Atacama Desert, Chile, South America: refinement of the dual isotopic compositions (δ15N vs. δ18O). Issue 1 (2nd January 2022) - Mizota, Chitoshi; Hansen, Robin; Hosono, Takahiro; Okumura, Azusa
ABSTRACT: Sodium nitrate ores from the Atacama Desert in South America were economically important as they represented huge natural resources for the fertilizer and explosives industries during the early nineteenth to early twentieth centuries. Nitrogen and oxygen isotope ratios ( δ 15 N and δ 18 O) of these desert nitrates generally show unique compositions (from close to 0 and up to ca. +50 ‰, respectively). The nitrates indicate the provenance as atmospheric in origin due to the mass-independent photochemical reaction of nitric oxide (NO) with ozone (O3 ) in the atmosphere to produce nitrate (NO3 – ). This paper examines the previously existing isotope data for specimens acquired from the Atacama Desert. It then reports new data from dual isotope analysis of historic nitrate specimens archived in museums in the UK. In the stable isotope signatures for nitrates from two areas of the Atacama Desert, Tarapacá in the north and Antofagasta in the south, were examined, and this analysis enabled a more detailed definition of their isotopic compositional ranges. This improved database is useful for tracing the provenance of the historic nitrates used in gunpowder and saltpetre, and also the cause of nitrate pollution in natural environments for which routine chemistry alone cannot provide the definite evidence for the origin.